Sexual and non-sexual social preferences in male and female white-eyed bulbuls - Bekir Kabasakal (Nature Portfolio, 2017)
Abstract While the function of ornaments shaped by sexual selection is to attract mates or drive off rivals, these signals may also evolve through social selection, in which the social context affects the fitness of signallers and receivers. Classical ‘mate choice’ experiments often reveal preferences for ornaments, but few studies have considered whether these are strictly sexual or reflect general social preferences. Indeed, an alternative possibility is that ornaments evolve through ‘non-sexual social selection’ (hereafter ‘social selection’). We examined the role of ornamentation (yellow ventral patch) and familiarity (individuals recognize group mates with which they have had previous interactions) on mate choice (opposite-sex stimuli preference) and social choice (same-sex stimuli preference) in both male and female white-eyed bulbuls (Pycnonotus xanthopygos). In the mate choice test, females preferred unfamiliar males with increased yellow. There were no biologically important differences in male preferences based on familiarity or intensity of patch colour. In the social choice test, females preferred to associate with familiar females. Males preferred to associate with familiar males but also preferred to associate with less ornamented males. Our results suggest that ornamentation and familiarity are important features, playing different roles in males and females, in both social and sexual selection processes.